Study on the Properties and Pest Control Effects of Five Common Wheat Flour Packaging Materials - HE Rui; ZHANG Feng; ZHANG Yuan-quan; CHEN Jin-shen; LV Jian-hua (Liang you shipin ke-ji)
This study investigated the physical properties and pest resistance of five common packaging materials. Tests were conducted on tensile properties, right-angle tearing strength, puncture resistance, combustion performance, friction coefficient, drop resistance, pressure resistance, and sealing performance. Pest resistance was evaluated using adult Tribolium castaneum (Herbst), adult Lasioderma serricorne (Fabricius), and newly hatched larvae of L. serricorne. The results showed that, in terms of mechanical properties, woven bags and aluminum foil bags exhibited superior tensile, tear, and puncture resistance. However, when used as packaging bags, non-woven fabrics and woven bags demonstrated better performance in friction, drop, and pressure resistance. All five packaging materials effectively protected wheat flour from stored grain pests, with vacuum plastic bags and aluminum foil bags providing complete protection.